The Romanian ichthyological researches on the continental shelf of U.S.A. in 1978 - Staicu, Ionel (Cercetări Marine - Recherches Marines, 2026)
The work presents the results of the observations on the Romanian fishing on the continental shelf of U.S.A. in October-December 1978, including data on the catches, composition by species, structure by length class, weight, sexes and age of the main species that have been caught.